ISLAMIC ECONOMY PHILOSOPHY IN KINALIZADE ALI ÇELEBI PERSPECTIVE - Rifqi Khairul Anam (LPPM STAI Muhammadiyah Probolinggo, 2024)
Kinalizade Ali Çelebi was a prominent scholar of the Ottoman Empire. During that time, he taught in several schools and served as a magistrate in a number of administrative centers. Kinalizade Ali Çelebi was a multifaceted scholar who contributed to science and published works on philosophy, religion, Sufism, ethics, history, language, and literature. Kinalizade Ali Çelebi's book, Ahl al-'Alaī, provides a comprehensive discussion of Islamic ethics and economics. Other works, however, have persisted to the present day in the form of manuscripts that have not been subjected to scientific investigation. This report aims to inform future research on the critical edition and publication of Kinalizade Ali Çelebi's manuscripts. This paper will help promote Kinalizade Ali Çelebi's philosophical work. This qualitative descriptive research analyzes Kinalizade Ali Çelebi's thought and related material. This paper explores the foundations of Kinalizade Ali Çelebi's Islamic Economic Philosophy